Xenopericardial self-made tube grafts in infectious vascular reconstructions: Preliminary results of an easy and ready to use surgical approach - Zientara, Alicja; Schwegler, Igor; Dzemali, Omer; Bruijnen, Hans; Peters, Andreas; Attigah, Nicolas (Vascular, 2016)
PurposeInfections are a major setback of vascular reconstruction and associated with considerable morbidity and mortality. We evaluated retrospectively our results with self-made bovine pericardial grafts in infected vessel revascularization versus standard graft material.Basic methodsRetrospective analysis of 9 patients with bovine reconstruction and 10 patients with miscellaneous grafts (vein, homograft) for vascular infections.Principal findingsInfection-free rate of the pericardial group was 100% in 17 months. For patients after reconstructions with miscellaneous grafts, the infection-free rate was 82% in 45 months. Overall in-hospital mortality was 10.5%. There were no in-hospital deaths in the pericardial group. Graft patency of the whole cohort was 100%. The median follow up was 11.74 months.ConclusionSelf-made bovine pericardial tube grafts can be crafted to almost any size and adjusted to complex anatomic requirements. The use was feasible in various situations and was associated with good preliminary results concerning patency and reinfection.